Biodistricts as a tool to revitalize rural territories and communities: insights from the biodistrict Cilento - Stefanovic, Lilliana; Agbolosoo-Mensah, Ohemaa Achiaa (Frontiers in Sustainable Food Systems, 2023)
The necessity and urgency of the food systems transformation is no longer questionable, and the transformation pathways are inevitably reappearing as a subject of academic and public debate. In search of sustainable food production strategies as part of a broader transformation, organic food systems are called for as one of the solutions to achieve environmentally friendly and just food systems. In this context, the role of biodistricts has been recently emphasized at the EU level. The authors of the manuscript argue that biodistricts, aside from acting as a tool to help achieve the EU target of increasing the share of organically farmed land, are also capable of revitalizing rural territories and communities, which are currently threatened with rural exodus. Semi-structured interviews and the focus group with key actors of the biodistrict Cilento revealed a multitude of territory- and community related outcomes, which demonstrate that organic districts are capable of rendering rural territories to attractive multifunctional spaces with a tight-knit community.